Lean management practices and its effect on Malaysian local government performance / Nur Ain Abu Bakar …[et al.] - Abu Bakar, Nur Ain; Tuan Mat, Tuan Zainun; Mohd Fahmi, Fadzlina; Tajul Urus, Sharina (Universiti Teknologi MARA Cawangan Selangor, 2017)
The application of Lean Management practice in the public sector, specifically in local government, has gained attention for overcoming the criticism received regarding the poor performance of organisations and poor service delivery offered. Lean Management practices have become among one of the approaches taken to increase performance and have been gaining more attention from public sectors. The purpose of this study is to examine the effect of Lean Management practices in local government on its productivity and service delivery performance to the public. This study focuses on three Lean Management practices, which are 5-S, kaizen, and Value Stream Mapping. It is important to assess the Lean Management practice encompassing each of these three elements in the relation to organizational performance, as it is one of the operational stability quality movement tools in the service sector. Data is collected from the local government. i.e., city councils located in Peninsular Malaysia. The data were obtained from the questionnaire survey distributed to employees in various city council in Peninsular Malaysia. Results showed that 5-s is the most common practice in local government followed by value stream mapping and kaizen. Regression analysis showed that, lean management practices in local government significantly affect service delivery performance of the organization. This indicates that the implementation of lean management as one of the quality improvement applications in the public sector, significant effect in improving their productivity and service delivery.